Repair of Extrahepatic Bile Duct Defect Using a Collagen Patch in a Swine Model. Issue 4 (27th October 2014) - Tao, Liang; Li, Qiang; Ren, Haozhen; Chen, Bing; Hou, Xianglin; Mou, Lingjun; Zhou, Siqiao; Zhou, Jianxin; Sun, Xitai; Dai, Jianwu; Ding, Yitao
Abstract Extrahepatic bile duct (EBD) injury can happen during surgery. To repair a defect of the EBD and prevent postoperative biliary complications, a collagen membrane was designed. The collagen material was porous, biocompatible, and degradable and could maintain its shape in bile soaking for about 4 weeks. The goal was to induce rapid bile duct tissue regeneration. Twenty Chinese experimental hybrid pigs were used in this study and divided into a patch group and a control group. A spindle‐shaped defect (20 mm × 6 mm) was made in the anterior wall of the lower EBD in the swine model, and then the defect was reconstructed using a collagen patch with a drainage tube and wrapped with greater omentum. Ultrasound was performed at 2, 4, 8, and 12 weeks postoperatively. Liver function tests and white blood cell count (WBC) were measured. Hematoxylin–eosin staining, cytokeratin 7 immunohistochemical staining, and Van Gieson's staining of EBD were used. The diameter and thickness of the EBD at the graft site were measured. There was no significant difference in liver function tests or WBC in the patch group compared with the control group. No evidence of leakage or stricture was observed, but some pigs developed biliary sludge or stone at 4 and 8 weeks. The drainage tube was lost within 12 weeks. The neo‐EBD could withstand normal biliary pressure 2 weeks after surgery. Histological study showed the accessory glands and epithelial cells gradually regenerated at graft sites from 4 weeks, with increasing vessel infiltration and decreasing inflammation. The collagen fibers became regular with full coverage of epithelial cells. The statistical analysis of diameter and thickness showed no stricture formation at the graft site, but the EBD wall was slightly thicker than in the normal bile duct due to collagen fiber deposition. The structure of the neo‐EBD was similar to that of the normal EBD. The collagen membrane patch associated with a drainage tube and wrapped with greater omentum effectively induced the regeneration of the EBD defect within 12 weeks.